BEST PRACTICES FOR CURRICULUM PLANNING AND EVALUATION AT SMKN 2 MARABAHAN - Sherwina Ranisa; Hairullah; Rama Meiagriza; Besse Maryani; Nor Azizah; Agus Syukran; Suhaimi; Muhammad Saleh (SOSIOEDUKASI, 2026)
This study aims to describe best practices in curriculum planning, implementation, evaluation, and follow-up at SMK Negeri 2 Marabahan. The research focuses on understanding how curriculum management is carried out systematically, collaboratively, and adaptively to meet industry needs and technological developments. A descriptive qualitative approach was employed, and data were collected through in-depth interviews, observations, and document analysis with three key informants: the principal, the vice principal for curriculum, and a teacher. Data were analyzed using the Miles, Huberman, and Saldaña model, consisting of data condensation, data display, and conclusion drawing/verification. The findings indicate that curriculum planning is collaboratively conducted through industry needs assessment and student competency analysis, ensuring alignment with the link-and-match principle. Curriculum implementation includes project-based learning, field practice, and contextual approaches to balance cognitive, affective, and psychomotor competencies. Evaluation is conducted using the CIPP (Context, Input, Process, Product) model, followed by program revision, teacher capacity building, and strengthened industry partnerships. The study concludes that effective curriculum management is supported by visionary leadership, strong collaboration, active stakeholder participation, and commitment to continuous improvement. These findings may serve as a reference for vocational schools seeking to develop adaptive curriculum practices.